The 2030 architecture of Association of Southeast Asian Nations Free Trade Agreements - Suthiphand Chirathivat; Piti Srisangnam (Asian Development Bank Institute (ADBI), 2013)
This paper investigates and analyzes the present status, potential, and prospects of Association of Southeast Asian Nations (ASEAN) free trade agreements (FTAs). It begins with a review of the historical evolution of ASEAN FTAs, which captures the achievements of the ASEAN Free Trade Agreement (AFTA) and the efforts meant to lead to a further step of deeper integration, i.e., the realization of the ASEAN Economic Community (AEC) by 2015. The paper then offers a view on how the grouping adopted an extension of ASEAN FTAs beyond the AEC - a widening integration process that includes ASEAN+1 FTAs, bilateral trading arrangements, and region-wide economic integration. These parallel developments present major challenges to ASEAN, particularly the move towards the AEC by 2015 and the attempts to broaden FTAs in East Asia. Ultimately, it is desirable for ASEAN to draw a clear picture of how the architecture of ASEAN FTAs in 2030 can be given shape.
Keywords: F13; F14; F15; 330; nafta; trade; free trade agreements; fta; regional integration; asean; asean economic community; aec; Freihandelszone; Regionale Wirtschaftsintegration; Handelsabkommen; Wirtschaftswachstum; ASEAN-Staaten